let X be non empty set ; :: thesis: for Y being ComplexNormSpace
for f, g, h being Point of ()
for f9, g9, h9 being bounded Function of X, the carrier of Y st f9 = f & g9 = g & h9 = h holds
( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) )

let Y be ComplexNormSpace; :: thesis: for f, g, h being Point of ()
for f9, g9, h9 being bounded Function of X, the carrier of Y st f9 = f & g9 = g & h9 = h holds
( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) )

let f, g, h be Point of (); :: thesis: for f9, g9, h9 being bounded Function of X, the carrier of Y st f9 = f & g9 = g & h9 = h holds
( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) )

let f9, g9, h9 be bounded Function of X, the carrier of Y; :: thesis: ( f9 = f & g9 = g & h9 = h implies ( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) ) )
assume A1: ( f9 = f & g9 = g & h9 = h ) ; :: thesis: ( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) )
A2: now :: thesis: ( ( for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) ) implies f - g = h )
assume A3: for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) ; :: thesis: f - g = h
now :: thesis: for x being Element of X holds (h9 . x) + (g9 . x) = f9 . x
let x be Element of X; :: thesis: (h9 . x) + (g9 . x) = f9 . x
h9 . x = (f9 . x) - (g9 . x) by A3;
then (h9 . x) + (g9 . x) = (f9 . x) - ((g9 . x) - (g9 . x)) by RLVECT_1:29;
then (h9 . x) + (g9 . x) = (f9 . x) - (0. Y) by RLVECT_1:15;
hence (h9 . x) + (g9 . x) = f9 . x by RLVECT_1:13; :: thesis: verum
end;
then f = h + g by ;
then f - g = h + (g - g) by RLVECT_1:def 3;
then f - g = h + () by RLVECT_1:15;
hence f - g = h by RLVECT_1:4; :: thesis: verum
end;
now :: thesis: ( h = f - g implies for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) )
assume h = f - g ; :: thesis: for x being Element of X holds h9 . x = (f9 . x) - (g9 . x)
then h + g = f - (g - g) by RLVECT_1:29;
then h + g = f - () by RLVECT_1:15;
then A4: h + g = f by RLVECT_1:13;
now :: thesis: for x being Element of X holds (f9 . x) - (g9 . x) = h9 . x
let x be Element of X; :: thesis: (f9 . x) - (g9 . x) = h9 . x
f9 . x = (h9 . x) + (g9 . x) by A1, A4, Th20;
then (f9 . x) - (g9 . x) = (h9 . x) + ((g9 . x) - (g9 . x)) by RLVECT_1:def 3;
then (f9 . x) - (g9 . x) = (h9 . x) + (0. Y) by RLVECT_1:15;
hence (f9 . x) - (g9 . x) = h9 . x by RLVECT_1:4; :: thesis: verum
end;
hence for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) ; :: thesis: verum
end;
hence ( h = f - g iff for x being Element of X holds h9 . x = (f9 . x) - (g9 . x) ) by A2; :: thesis: verum